Analyses of the 2020 Nobel Prize in Physiology or Medicine: Taking the Hepatitis C Virus from Mystery Killer to Preventable and Treatable Disease. Issue 1 (2nd January 2021) - Gilman, Neyda
ABSTRACT: Harvey J. Alter, Michael Houghton, and Charles M. Rice share the 2020 Nobel in Physiology or Medicine for their contributions to the identification, treatment, and eventual elimination of the hepatitis C virus (HCV). The then novel molecular techniques they used have laid the groundwork for future work on HCV and other viruses. This article will give a brief overview of the hepatitis disease and the work of this year's laureates. It will also take a bibliometric look at the scientist's research and add to the discussions about the way modern science is done and the limitations of prestigious science awards being awarded to only three awardees.